A novel top-n recommendation method for multi-criteria collaborative filtering. (15th July 2022) - Kaya, Tugba; Kaleli, Cihan
Abstract: Most online service providers utilize a recommender system to help their customers' decision making process by producing referrals. If a customer requests a suggestion for a specific item, the recommender systems produce predictions for it. On the other hand, it is also possible to create top- n lists containing the products that the customer might like the most. Recommender systems' outcomes depend on individuals' preferences which can be provided by considering a single criterion or multiple criteria about the services or products. Therefore, there must be methods to produce predictions and top- n lists for single and multiple-criteria datasets. Although the researchers introduced several algorithms on single criterion-based ratings for producing single predictions and top- n lists, there are only methods for producing referrals for a specific item on multi-criteria data. Accordingly, this paper proposes an intuitionistic fuzzy set-based top- n recommender system method with a novel neighborhood formation process for multi-criteria datasets. The proposed method consists of two crucial points: (i) Determining the relational structure between products; (ii) Investigating user tendencies, as well as their distinctive structures and rating distributions. The rating distribution and the relational structure between the products are determined with association rule mining and entropy measure, while the attitudes and tendencies of the users during the evaluation are analyzed with intuitionistic fuzzy sets. We also adopt a single-criterion top- n method to a multi-criteria recommender system, and we employ crisp ratings instead of fuzzy ones to compare the performance of the proposed method. The measurements of serendipity, diversity, and novelty are utilized to show how the experimental results are compelling. When the experiments' results are examined, it is concluded that our method can generate successful top- n lists. Highlights: Novel multi-criteria top- n RS based on a new neighborhood selection process (NSP) is developed. The new NSP based on the different properties of the products is applied using entropy and ARM. Effective analysis of products and users has improved the quality of the RS. The criteria weighting is carried out using entropy.